Use of low-cost chemotherapeutic and medicinal plants against Thai silver barb (Barbonymus gonionotus) (Journal of the Bangladesh Agricultural University, 2013)
Studies were conducted to select and apply the effective low-cost chemotherapeutic and medicinal plants against diseased fish under laboratory and field condition. Thai silver barbs (Barbonymus gonionotus) weighing 20-25 gm were experimentally infected with a virulent bacterial pathogen (Aeromonas hydrophila) and a fungal pathogen (Aphanomyces invadans). Based on the previous studies, four chemotherapeutics, viz., salt + lime, alum, doxycycline and oxytetracycline were selected and applied to observe the therapeutic effects under laboratory and field condition. In the case of medicinal plants, leaves/ bulb / seeds/ rhizome of neem (Azadirachta indica), akand (Calotropis gigantea), garlic (Allium sativum), turmeric (Curcuma longa), shoti (Curcuma zedoaria), Indian sorrel (Oxalis corniculata), guava (Psidum guajava) and kalijira (Nigella sativa) were screened out and applied to the infected fish in laboratory and field condition to determine their efficacies. The antibiotics, both oxytetracycline and doxycycline were found to be very efficient followed by salt + lime and alum. For fungal infection, alum was excellent followed by salt + lime both under laboratory and field condition. Even in the pond trial, alum and salt + lime successfully checked the occurrence of epizootic ulcerative syndrome (EUS) and similar diseases. In the case of medicinal plants, neem and akand together reduced the occurrence bacterial and fungal disease. Garlic was very efficient to check bacterial infection but weak against fungal disease. Turmeric and arrowroot were found to be highly effective against fungal disease but moderately effective against bacterial disease. Field trial revealed that Indian sorrel and guava were highly efficient against bacterial disease but poorly efficient against fungal disease. On the other hand, arrowroot and black cumin were highly efficient against fungal disease but moderately efficient against bacterial disease. The results would be useful to the all concerned for proper health management of cultured fishes.DOI: http://dx.doi.org/10.3329/jbau.v10i2.14932 J. Bangladesh Agril. Univ. 10(2): 385-390, 2012